2021
DOI: 10.1016/j.ijid.2021.02.052
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of four SARS-CoV-2 antigen tests in hospitalized patients

Abstract: Objectives Rapid identification of infected subjects is a corner stone for control of a pandemic like the current one with the SARS-CoV-2. Easy to handle antigen tests can provide timely results which is of specific importance in a primary care setting. However, concerns exist regarding their sensitivity, which let us evaluate four commercially available tests in patients hospitalized for COVID-19. Methods We analyzed in parallel nasopharyngeal/oropharyngeal swabs from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…However, after the analyses of Ct values, it can be seen that subjects that were both antigen and RT-qPCR positive had mean and median Ct values for Sarbeco E and RdRP genes amounting to about 20, whereas the antigen-negative but RT-qPCR-positive samples had these measures of centre close to 30 (details are in Table 2). The inability to detect samples with higher Ct values is in line with the results of Thommes et al When investigating subjects with Ct values higher than 30, the antigen tests were positive in no more than 45% of such cases [17]. If the cycle threshold (Ct) values are taken as viral load indicators and prediction markers [32][33][34], it may be considered a strength of this antigen test (Standard Q COVID-19 Ag test, SD Biosensor) that it detects people at higher risk both on the personal level (risk of more severe disease) and on the population level (risk of viral shedding and transmission).…”
Section: Antigen Testingsupporting
confidence: 79%
See 1 more Smart Citation
“…However, after the analyses of Ct values, it can be seen that subjects that were both antigen and RT-qPCR positive had mean and median Ct values for Sarbeco E and RdRP genes amounting to about 20, whereas the antigen-negative but RT-qPCR-positive samples had these measures of centre close to 30 (details are in Table 2). The inability to detect samples with higher Ct values is in line with the results of Thommes et al When investigating subjects with Ct values higher than 30, the antigen tests were positive in no more than 45% of such cases [17]. If the cycle threshold (Ct) values are taken as viral load indicators and prediction markers [32][33][34], it may be considered a strength of this antigen test (Standard Q COVID-19 Ag test, SD Biosensor) that it detects people at higher risk both on the personal level (risk of more severe disease) and on the population level (risk of viral shedding and transmission).…”
Section: Antigen Testingsupporting
confidence: 79%
“…Under regulations issued by the Ministry of Health of the Slovak Republic, hospital employees are obliged to undergo testing using state-supplied antigen tests every second week. However, many questions were raised about the suitability of the selected testing method, especially regarding its use with large numbers of healthcare professionals and its effectiveness where individuals have low viral load [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our study we have considered Ct value of 35 on RT-PCR as positive. However, with Ct values of 25 which corresponds to high viral load, conventional card based antigen detection tests (RAT) shows better sensitivity ( Thommes et al, 2021 ; Pickering et al, 2021 ). Therefore, we also evaluated the performance of VITROS, and RAT based on Ct value of 25.…”
Section: Resultsmentioning
confidence: 99%
“…However, one investigated test had a poor clinical performance. 155 Bruzzone et al have quantified the performance of seven different available types of antigendetecting rapid diagnostic tests compared with RT-qPCR, and the results showed that the overall sensitivity and specificity of antigen tests were 78.7% and 100%, respectively, and a wide range of sensitivity of different brands (66.0-93.8%) was observed. 156 Therefore, further investigations and confirmatory studies are needed for the validation of different antigendetection kits.…”
Section: Antigen Testingmentioning
confidence: 99%